Evaluation of lime plaster on masonry walls in historical buildings prior to renovation - Adrian Chajec; Anna Hoła; Jerzy Hoła; Łukasz Sadowski (Budownictwo i Architektura)
This study analysed a quantitative assessment of the adhesion of lime plasters to the substrate in a historic neo-Gothic building. The diagnostics of the plasters were conducted to preserve their large surface area due to their historical value. The use of modern non-destructive and destructive methods allowed for a significant reduction in the work required to remove the historic plaster. It was noted that only the correlation of non-destructive and destructive methods can enable an accurate determination of the necessary repair work on historic plasters. Challenges in diagnosing plasters in historic buildings are also discussed.